Systematisk inledning till Nordisk lexikografisk ordbok (NLO) - Bergenholtz, Henning; Svensén, Bo (LexicoNordica, 1994)
One of the major problems of LSP lexicography is connected with the fäet that an alphabetic macrostructure is not able to present a systematic overview of the subject field covered by the dictionary. Therefore, some modem dictionaries are provided with an encyclopedic section which constitutes a separate dictionary component giving an introduction to, or a systematic and detailed exposition of, the subject. This contribution presents an encyclopedic section meant to be included in the planned Nordic Lexicographical Dictionary.